Applied Implications of Understanding the Natural Development of Effortful Control. (October 2018) - Durbin, C. Emily
Effortful control (EC) is an important target for many interventions intended to facilitate positive psychosocial outcomes. The first wave of these efforts has emphasized adult-to-child instruction and individualized practice of target skills. Future tests of these ideas will be facilitated by efforts to critically evaluate and improve the construct validity of EC measures. New avenues for these applied approaches will also grow out of a more complete understanding of the processes that govern EC development. Specifically, I argue that the natural development of EC includes important roles for contextual and peer relationship factors that have yet to be capitalized on in efforts to increase EC in children.